1990
DOI: 10.1029/jb095ib04p04405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite diagenesis in marine sediments from the Oregon continental margin

Abstract: The magnetochemistry of sediments from the Oregon continental margin is examined to determine the effects of iron-sulfur diagenesis on the paleomagnetic record. Magnetic mineral dissolution and lxansformation into iron sulfides are a common feature in these suboxic to anoxic lutites. These processes are evidenced in rapid decreases in natural reinanent magnetization intensities and stabilities, systematic changes in other rock magnetic properties, and increases in solid phase sulfur concentrations with depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(97 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…LIPPERT AND ZACHOS: BIOGENIC MAGNETITE AT THE PETM pelagic and hemipelagic sections [Karlin, 1990b;Tarduno and Wilkison, 1996]. Saturation magnetization (M s ) and squareness (M rs /M s ) remain relatively low throughout the latest Paleocene and then rise abruptly with the onset of the CIE at 109.85 m (Figure 2).…”
Section: Pa4104mentioning
confidence: 99%
“…LIPPERT AND ZACHOS: BIOGENIC MAGNETITE AT THE PETM pelagic and hemipelagic sections [Karlin, 1990b;Tarduno and Wilkison, 1996]. Saturation magnetization (M s ) and squareness (M rs /M s ) remain relatively low throughout the latest Paleocene and then rise abruptly with the onset of the CIE at 109.85 m (Figure 2).…”
Section: Pa4104mentioning
confidence: 99%
“…), that may destroy or mask the primary geochemical signals (Shenetger et al, 2000;Rao et al, 2008). On the other hand, rock magnetic parameters (concentration, mineralogy and grain size) of the sediments respond to environmental change and have been used extensively to address provenance, climate-related and diagenetic changes (Karlin, 1990;Bloemendal et al, 1988;Leslie et al, 1990;Vigliotti et al, 1999). It has been shown that the variations in magnetic susceptibility are related to global oxygen isotope fluctuations (Vigliotti, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…variations in organic matter, sedimentation rate). Resulting genetic mixtures of magnetic minerals potentially range from unaltered to entirely authigenic in origin [Karlin, 1990]. It is a complex and site-specific task to untangle the magnetic signal [Urbat et al, in press], yet bears a great potential to study diagenetic behavior.…”
Section: Introductionmentioning
confidence: 99%